The gifts of imperfection - Brown, Brené, ....- (Minnesota : Hazelden, 2020)
For over a decade, Brené Brown has found a special place in our hearts as a gifted mapmaker and a fellow traveler. She is both a social scientist and a kitchen-table friend whom you can always count on to tell the truth, make you laugh, and, on occasion, cry with you. And what's now become a movement all started with The Gifts of Imperfection, which has sold more than 3 million copies in 35 different languages across the globe. What transforms this book from words on a page to effective daily practices are the ten guideposts to wholehearted living. The guideposts nog only help us understand the practices that will allow us to change our lives and families, they also walk us through the unattainable and sabotaging expectations that get in the way.
Keywords: Levenskunst